PENGARUH MEDIA PEMBELAJARAN BERBASIS DIGITAL TERHADAP HASIL BELAJAR SISWA (Studi Survei di SMA Negeri 72 Jakarta) - Nurhasan Alfarizi; Nadiah; Husheini Fadhil; Fadil Nurdiansyah; Choiruddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the still-conventional learning methods commonly used in schools, which can affect student learning outcomes, so that active and innovative learning media such as Quizizz are needed. Quizizz is an interactive learning medium that creates an enjoyable learning atmosphere through game-based quizzes and is expected to significantly improve student learning outcomes. This study aims to determine the influence of digital-based learning media (Quizizz) on student learning outcomes at SMA Negeri 72 Jakarta. A quantitative method with a survey approach was used, involving a population of 251 eleventh-grade students, with 38 students selected as the sample through cluster sampling. Data were collected using questionnaires, observation, and documentation, and analyzed using the Pearson Product Moment technique. The results show a Product Moment correlation coefficient of 0.522 between Digital-Based Learning Media (X) and Student Learning Outcomes (Y), which is higher than the r-table value at the 5% significance level (0.316) and the 1% significance level (0.408). Because ro > rt at both levels, the Alternative Hypothesis (Ha) is accepted and the Null Hypothesis (Ho) is rejected. The coefficient of determination shows that digital-based learning media contributes 27.2% to student learning outcomes. It is concluded that digital-based learning media has a positive and moderately strong influence on student learning outcomes at SMA Negeri 72 Jakarta.